2020
DOI: 10.1177/0003489420936710
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Injuries from Rock Climbing: A Query of the National Electronic Injury Surveillance System

Abstract: Objective: We describe the incidence and characteristics of patients with head and neck injuries from rock climbing who present to United States emergency departments and evaluate predictors of hospitalization. Methods: The National Electronic Injury Surveillance System (NEISS) database was queried for rock climbing injuries to the head, face, mouth, neck, and ear under product code “mountain climbing” from the years 2009 to 2018. Demographics, injury characteristics, and disposition data were reviewed. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The NEISS database has been used in prior epidemiological studies in otolaryngology to obtain national estimates of the incidences of injury-related ED visits. 10-13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NEISS database has been used in prior epidemiological studies in otolaryngology to obtain national estimates of the incidences of injury-related ED visits. 10-13…”
Section: Methodsmentioning
confidence: 99%
“…The NEISS database has been used in prior epidemiological studies in otolaryngology to obtain national estimates of the incidences of injury-related ED visits. [10][11][12][13] The NEISS database was searched for patients with facial fractures associated with all available sports and recreation product and activity codes. Of these, cases with reported nose or nasal fractures were extracted and analyzed after adjusting for statistical weight.…”
Section: Methodsmentioning
confidence: 99%
“…The NEISS database has been used in prior epidemiological studies in otolaryngology to obtain national estimates of the incidences of injury-related ED visits. 10-13…”
Section: Methodsmentioning
confidence: 99%
“…The author uses Excel 2016 and SPSS16.0 to statistically process the data of each indicator obtained by the test, and uses the Shapiro-Wilk (W test) to test the data, and it is concluded that the distribution of each data indicator is a normal distribution, 8 bivariate was used to analyze the correlation between each basic physical fitness index and the special index of rock climbing after the experiment. 9…”
Section: ) Mathematical Statisticsmentioning
confidence: 99%